2019
DOI: 10.1097/iae.0000000000002325
|View full text |Cite
|
Sign up to set email alerts
|

Facedown Positioning After Vitrectomy Will Not Facilitate Macular Hole Closure Based on Swept-Source Optical Coherence Tomography Imaging in Gas-Filled Eyes

Abstract: Purpose: To compare clinical outcomes in eyes with macular hole (MH) managed by either facedown (FD) or no-FD (nFD) postoperative positioning protocols. Methods: This is a prospective randomized cohort study. Eighty eyes of 80 consecutive patients with MH who had undergone vitrectomy surgery with internal limiting membrane peeling and gas tamponade were included in this study. Forty eyes of 40 patients who were kept in FD position for 3 days after surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Of these 34 reports, 8 were not RCTs, 2 did not apply ILM peeling, and 19 did not include a comparison group, and were excluded from the meta-analysis as they did not meet the inclusion criteria. The remaining 5 RCTs were included in the final meta-analysis [ 14,[18][19][20][21]. The trial selection process is summarized in Fig.…”
Section: Search Results and Characteristics Of The Studiesmentioning
confidence: 99%
“…Of these 34 reports, 8 were not RCTs, 2 did not apply ILM peeling, and 19 did not include a comparison group, and were excluded from the meta-analysis as they did not meet the inclusion criteria. The remaining 5 RCTs were included in the final meta-analysis [ 14,[18][19][20][21]. The trial selection process is summarized in Fig.…”
Section: Search Results and Characteristics Of The Studiesmentioning
confidence: 99%
“…Of these 34 reports, 8 were not RCTs, 2 did not apply ILM peeling, and 19 did not included a comparison group, so they were excluded from the meta-analysis owing to conflict with the inclusion criteria. The remaining 5 RCTs were included in the final meta-analysis [14,[18][19][20][21]. The trial selection process is summarized in Fig.…”
Section: Search Results and Characteristics Of The Studiesmentioning
confidence: 99%
“…Previous studies have reported that the healing of MHs begins within 24 hours after the surgery, and the bridge configuration occurs around 3 days [30,31]. The MHs were basically healed within 3 days after the surgery, and those that were not healed within 3 days were still open during the 3-month follow-up [3,21]. All of the studies included in this meta-analysis were in the prone position for 3 days or more, so the comparison of the closure rate of the MHs with sizes larger than 400 µm in the FDP and nFDP groups after MH surgery is credible.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations